A REFLECTION AND CRITIQUE ON THE TRANSFORMATIONS OF THE PUBLIC SPACE OF THE CITY OF SALVADOR, BAHIA: SHARED STREETS AND COMPLETE STREETS AS URBAN INTERVENTION - Macedo, Rodrigo Rodrigues Coutinho de Carvalho (Seven Editora, 2025)
The public space intended for the circulation, socialization, coexistence and permanence of pedestrians. In it, as a social product, it is under a continuous process of transformation at every need. The use of vehicles in cities changed the cycle of socialization and the transformations of public and private values, as well as contributed to the emptying and abandonment of public space (squares, parks and gardens), streets began to be shaped on an automobile scale, generating conflict between the circulation of vehicles and people and safety on public roads. On the other hand, due to these factors, the concepts of Shared space, traffic calming, shared streets, complete streets and others as urban interventions emerged. This article addresses the reflection on the transformations of the public space of the city of Salvador, conceptualizing them, presenting their characteristics, challenges, criticisms, in addition to addressing the theory of the normative approach. A literature review and comparative data analysis were used as a methodology. Therefore, a reflection and a critique are made regarding these interventions and an alert about the types of streets and their context. DOI: https://doi.org/10.56238/sevened2025.018-029